Museologia e memória do Museu/Arquivo histórico da Santa Casa Dr. Alípio Bordalo de Belém-PA - VERÍSSIMO, Wanderlena do Socorro Corrêa (2019)
The Museum Archives / History of Santa Casa Dr. Alipio Bordallo of Belém do Pará is a museum that preserves the history and memory of an institution that has 363 years of service to society Para. Being the Santa Casa de Misericordia, institutional model of care to the needy created in Italy in the twelfth century, became action tag of the Portuguese crown. The same was implemented in Brazil in 1543, in Santos and Para in 1650. When was Holy House of Mercy of Pará, founded on the present town of Bethlehem Changing name by state interventions, the Santa Casa de Misericordia Para officiated this name in 1990. The Santa Casa founded on June 22, 1987 a museum that aims to rescue the history and memory of Para Medical Sciences. Museum that has a variety of collections, with a total of 15 collections. Soon the purpose of this work lies in the possibility of improving the knowledge about the reality of this museum institution, establishing a union between their official history and the memories of people who worked in this institution. This work intends, through the eyes of Museology and its theoretical principles, emphasizing the reality of museological institution and processes that are present in the same well as "rescue" the memory of people who worked in this museum, as Dr. Alipio Bordallo , MSc. Euler Arruda and Dr. Márcio Henrique Couto.